Perbandingan Pendapatan Petani Jagung Anggota Dan Non Anggota Kelompok Tani Di Kecamatan Bandar Sribhawono Lampung Timur - Damayanti, Nabila; Humaidi, Edy; Irawati, Luluk; Anggraini, Nuni (Program Studi Pengelolaan Agribisnis, 2024)
Most Sripendowo villagers are corn farmers with hybrid and superior varieties, but corn productivity is still low. The Anugrah Tani farmer group provides training to increase productivity, but not all farmers are interested in joining. This study aims to identify the role of farmer groups, analyze, and compare the income of farmer members and non-members. Samples were taken by Proportional Random Sampling and analyzed descriptively and quantitatively. The results show that farmer groups play a role as a provider of production inputs and technology transfer. Farmer income of farmer group members reached Rp9,695,966/ha/growing season, higher than that of non-member farmers at Rp5,729,038/ha/growing season. The t-test showed a significant difference, confirming the positive contribution of farmer groups to increasing maize farmers' income.